Oedipus Rex [opera-oratorio in two acts] - Stravinsky, Igor 1882-1971 (State Academic Mariinsky Theatre, 2010)
Valery Gergiev conducts a new recording of Stravinsky's iconic neo-classical oratorio Oedipus Rex, complete with Jean Cocteau's original French narration spoken by Gerard Depardieu